Conflict Management Intentions of University Library Staff in Ghana - Kofi, Yaw Christian (Ghana Library Journal, 2004)
The article is an in-depth treatment of the various conflict management approaches. The case studies are the three ’oldest’ university libraries in Ghana with regard to their conflict management intentions. The objective was to assess the primary conflict management intentions of university library staff in Ghana. The article recommends that librarians must be flexible and be able to switch from one approach to another depending upon the nature of the conflict.